Intra-Operative Anastomotic Leak Rates and Testing Methodology in Colorectal Resection Surgery - Andrew Schiff; Brenna L Brady; Sudip K Ghosh; Sanjoy Roy; Charles Ruetsch; Elliott Fegelman (Journal of Surgery and Surgical Research - Peertechz Publications, 2016)
Purpose: Anastomotic leak following colorectal resection surgery is associated with high rates of morbidity, infection, and escalated healthcare expenditures. One method to prevent leaks includes early detection through intra-operative testing. This study employed systematic review of the literature to estimate the rate of intra-operative anastomotic leaks in colorectal resection surgery. Method: The Medline and Embase databases were searched to identify articles published between January 1st, 2003 and August 8th, 2015 reporting on intra-operative leaks in colorectal resection. The rate of intra-operative testing, intra- and post-operative anastomotic leaks, and surgical methodology were extracted from the final sample of 13 articles. Results: A total of 167 intra-operative leaks were reported within 2,598 colorectal resection surgeries that used intra-operative testing, yielding an average leak rate of 6.4%. Use of laparoscopic techniques was significantly associated with a reduced rate of intra-operative leak (p<0.001). Eight articles reported on the rate of post-operative anastomotic leak in relation to intra-operative testing. Within this sample of 2,098 cases a non-significant trend towards a lower leak rate in the tested population was identified (4.3% v. 6.8%, p=0.051); cases whose leak test was initially positive exhibited a significantly higher rate of post-operative leaks compared to cases with a negative leak test (p=0.006). Conclusion: Intra-operative anastomotic leak testing allows surgeons to address leaks at the time of surgery, and may help to prevent complications in colorectal resection surgery. This study identified a mean intra-operative leak rate of 6.4% in colorectal resection surgery.